Estimasi G-Study dalam Pengembangan Instrumen Penilaian Tahsinul Qur’an - Irfa Ma’alina Li’illiyyina; Badrun Kartowagiran (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This paper focuses on performance tests (performance tests) in the assessment of the Tahsin al-Qur'an certification exam using one rater in each assistance group. The assessment process that involves a rater on a performance test (performance test) has a great chance of giving birth to inconsistencies in giving rater assessments to different individuals with the same ability. This paper tries to solve this problem by developing instruments for two or more rater. This compilation process uses a quantitative analysis with generalizability theory approach and uses the help of the EduG version 6.1 program. This study shows that the examination of the tahsinul quran assessment instrument is said to be valid with aiken index value> 0.67 on each indicator. The reliability test on this instrument shows the reliability coefficient value> 0.80 for both limited and large sample trials. Based on these things, the assessment instrument of tahsinul quran can be said to be valid and reliable to measure the tahsin al-quran, and can minimize the subjectivity of the rater in making an assessment.